Pengaruh Indeks SSEC, N225, STI, dan Faktor Makroekonomi terhadap IHSG - Sebtian Dwi Prahesti; R.A Sista Paramita (Jurnal Ilmu Manajemen, 2020)
This study is to determine the effect of the exchange rate, inflation, the money supply, BI Rate, The Fed, SSEC (Shanghai Stock Exchange Composite Index), N225 (Nikkei 225), and STI (Strait Time Index) on the Composite Stock Price Index. The dependent variable is the CSPI (Y) and the independent variable of macroeconomic factors namely the exchange rate (X1), inflation (X2), money supply (X3), and BI Rate (X4), The Fed (X5), and the global index such as SSEC (X6), Nikkei 225 (X7), and STI (X8). This study implements multiple linear regression analysis methods of Statistical Package for Social Science. This study indicates that the exchange rate and the Strait Time Index influence the Composite Stock Price Index, while the inflation variable, the money supply, BI Rate, The Fed interest rate, the SSEC, and the Nikkei 225 dont affect the CSPI (Composite Stock Price Index). Inflation doesnt affect the CSPI because inflation in the research period is still relatively mild. The money supply doesnt affect the CSPI because people tend to use their money to invest in the money market rather than investing in shares. The BI rate doesnt affect CSPI because the BI Rate is not a parameter for investors in investing. The Fed doesnt affect CSPI because investors do not use The Fed Rate as a benchmark in investing. SSEC and N225 index dont affect the CSPI due to other factors outside the economy that affect the movement of the index.